A CO isotopologue Line Atlas within the Whirlpool galaxy Survey (CLAWS) - Brok, Jakob den; Bigiel, Frank; Sliwa, Kazimierz; Saito, Toshiki; Usero, Antonio; Schinnerer, Eva; Leroy, Adam K.; Jiménez-Donaire, María J.; Rosolowsky, Erik; Barnes, Ashley T.; Puschnig, Johannes; Pety, Jérôme; et al. (Astronomy and astrophysics, 2022)
We present the CO isotopologue Line Atlas within the Whirpool galaxy Survey (CLAWS), which is based on an IRAM 30 m large programme that provides a benchmark study of numerous faint CO isotopologues in the millimetre-wavelength regime across the full disc of the nearby grand-design spiral galaxy M 51 (NGC 5194). The survey’s core goal is to use the low-J CO isotopologue lines to constrain CO excitation and chemistry, and therefrom the local physical conditions of the gas. In this survey paper, we describe the CLAWS observing and data reduction strategies. We map the J = 1 → 0 and 2 → 1 transitions of the CO isotopologues 12CO, 13CO, C18O, and C17O, as well as several supplementary lines within the 1 mm and 3 mm window (CN(1-0), CS (2-1), CH3OH(2-1), N2H+ (1-0), and HC3N (10-9)) at ~1 kpc resolution. A total observation time of 149 h offers unprecedented sensitivity. We use these data to explore several CO isotopologue line ratios in detail, study their radial (and azimuthal) trends, and investigate whether changes in line ratios stem from changes in interstellar medium properties such as gas temperatures, densities, or chemical abundances. For example, we find negative radial trends for the 13CO/12CO, C18O/12CO, and C18O/13CO line ratios in their J = 1 → 0 transitions. We also find variations with the local environment, such as higher 12CO (2-1)/(1-0) or 13CO/12CO (1-0) line ratios in interarm regions compared to spiral arm regions. We propose that these aforementioned variations in CO line ratios are most likely due to a variation in the optical depth, though abundance variations due to selective nucleosynthesis on a galaxy-wide scale could also play a role. We also study the CO spectral line energy distribution (SLED) using archival JCMT 12CO (3-2) data and find a variation in the SLED shape with local environmental parameters, suggesting changes in the optical depth, gas temperatures, or densities.
Gesehen am 11.08.2022